Enhanced effects of reducing agent on oxalate chelated Fe(II) catalyzed percarbonate system for benzene degradation. Issue 1 (26th August 2021) - Fu, Xiaori; Wei, Xinyan; Zhang, Wei; Yan, Wupeng; Wei, Peng; Lyu, Shuguang
Abstract: The addition of hydroxylamine hydrochloride (HAH), ascorbic acid (ASC), sodium ascorbate (SAS) to the OA-Fe(II)/SPC system could promote the generation of HO by accelerating Fe(II)/Fe(III) recycles and H2 O2 decomposition. The enhancement of HAH on HO generation surpasses ASC and SAS in the OA-Fe(II)/SPC system. The generation of O2 − was also enhanced by HAH, ASC and SAS, and more significant promotion of O2 − generation was observed with ASC and SAS addition. More effective benzene removal was achieved in an OA-Fe(II)/SPC system with suitable HAH, ASC and SAS addition, compared to the parent system. Excessive HAH, ASC or SAS had a negative effect on benzene removal. Results of scavenger tests showed that HO is indeed the dominant free radical for benzene removal in every system, but the addition of HAH, ASC and SAS increased the contribution of O2 − to benzene degradation. HAH, ASC and SAS enhanced OA-Fe(II)/SPC systems could be well utilized to acidic and neutral conditions, while HCO3 −, high concentration of HA and alkaline conditions were not favorable to benzene removal. Moreover, the addition of HAH, ASC and SAS are conducive to benzene removal in actual groundwater, and HAH was the optimal reducing agent for the enhancement of the OA-Fe(II)/SPC system. HIGHLIGHTS: Benzene removal performance in an RA-OA-Fe(II)/SPC system was investigated. HAH is more conducive to HO generation than ASC and SAS. Significant promoted generation of O2 − was observed with ASC and SAS addition. HAH, ASC and SAS weakened negative effects of the solution matrix on benzene removal. HAH, ASC and SAS are conducive to benzene removal in actual groundwater.